Preliminary studies of selected Lemna species on the oxygen production potential in relation to some ecological factors - Sender, Joanna; Różańska-Boczula, Monika (PeerJ, 2024)
Dissolved oxygen is fundamental for chemical and biochemical processes occurring in natural waters and critical for the life of aquatic organisms. Many organisms are responsible for altering organic matter and oxygen transfers across ecosystem or habitat boundaries and, thus, engineering the oxygen balance of the system. Due to such Lemna features as small size, simple structure, vegetative reproduction and rapid growth, as well as frequent mass occurrence in the form of thick mats, they make them very effective in oxygenating water. The research was undertaken to assess the impact of various species of duckweed (L. minor and L. trisulca) on dissolved oxygen content and detritus production in water and the role of ecological factors (light, atmospheric pressure, conductivity, and temperature) in this process. For this purpose, experiments were carried out with combinations of L. minor and L. trisulca. On this basis, the content of oxygen dissolved in water was determined depending on the growth of duckweed. Linear regression models were developed to assess the dynamics of changes in oxygen content and, consequently, organic matter produced by the Lemna. The research showed that the presence of L. trisulca causes an increase in dissolved oxygen content in water. It was also shown that an increase in atmospheric pressure had a positive effect on the ability of duckweed to produce oxygen, regardless of its type. The negative correlation between conductivity and water oxygenation, obtained in conditions of limited light access, allows us to assume that higher water conductivity limits oxygen production by all combinations of duckweeds when the light supply is low. Based on the developed models, it was shown that the highest increase in organic matter would be observed in the case of mixed duckweed and the lowest in the presence of the L. minor species, regardless of light conditions. Moreover, it was shown that pleustophytes have different heat capacities, and L. trisulca has the highest ability to accumulate heat in water for the tested duckweed combinations. The provided knowledge may help determine the good habitat conditions of duckweed, indicating its role in purifying water reservoirs as an effect of producing organic matter and shaping oxygen conditions with the participation of various Lemna species.
Keywords: Dissolved oxygen; Duckweed; Organic matter; Temperature; Forecasting; Ecological factors